Advances in Nanostructured Cellulose-based Biomaterials - Carreño, Neftali L V.; Barbosa, Ananda M.; Noremberg, Bruno S.; Salas, Mabel M. S.; Fernandes, Susana C M.; Labidi, Jalel (SpringerBriefs in Applied Sciences and Technology,, 2017)
This book provides an overview of the advances on nanostructured celullose from different obtaining forms: natural plants and bacterial microorganisms. It gives the reader an introduction of cellulose focusing in nanosize particles, its potential applications and future perspectives. The potential use of cellulose in the biomedical field is highlighted.